Communication as the Study of Social Action: on the Study of Language and Social Interaction - Anita Pomerantz; Robert E. Sanders; Nicolas Bencherki (Communiquer)
In this interview, Anita Pomerantz and Robert E. Sanders, professors emeriti at the University at Albany, SUNY’s department of communication, discuss their views on conducting language and social interaction (LSI) research. They share their understanding of the connection between LSI research and the discipline of communication, and explain what we may gain from focusing on social action instead of solely studying messages. The relationship between an interaction and its context, and the way the latter may be relied on to analyze the former, is also discussed. To offer their insights, Pomerantz and Sanders draw from their active engagement, since the 1970s, as prominent voices of the language and social interaction community, and more particularly as figureheads of conversation analysis (CA).